TINJAUAN YURIDIS TINDAK PIDANA PENGEROYOKAN SECARA BERSAMA YANG MENGAKIBATKAN LUKA - Chantiqa Dwi Ayudhia Chaerunnisa; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
The defendant in the persecution case named Yayan Sopian bin Tardi has been sentenced proven and convincingly guilty of committing the crime of persecution as stipulated in Article 351 of Criminal Code. Through a brief research by the researcher, there are circumstances and a chronology of events which constitute the crime of beating up which resulted in injuries as stipulated in Article 170 Paragraph (2) 1st of Criminal Code. The formulation of the problems in this research are whether the defendant's actions were in accordance with Article 351 of the Criminal Code (Study of Decision Number 541/Pid.B/2020/PN Bdg) or not and what is the Judge’s Consideration in the Decision Number 541/Pid.B/2020/PN Bdg. This research is a normative and descriptive analytical legal research that use secondary data consisting of primary legal materials and secondary legal materials obtained from literature studies, analyzed qualitatively and the conclusions are drawn by using deductive logic methods. The conclusions from the research are 1) The defendant's actions were not in accordance with Article 351 Paragraph (1) in conjunction with Article 55 of the Criminal Code. 2) The considerations used in Decision Number 541/Pid.B/2020/PN Bdg are only based on artistic approach or intuition and wisdom.